Species composition and forestry characteristics of field shelterbelts established by G. M. Vysotsky in Ukrainian ravine steppe - Solomakha, N. G.; Korotkova, T. M.; Sydorenko, S. V.; Sydorenko, S. G.; Yurchenko V. А.; Tupchii, O. M. (Forestry and Forest Melioration, 2021)
Introduction The species composition of field shelterbelts is one of the main factors influencing the resilience and reclamation properties of linear protective plantings. The inconsistency of bioecological features of tree and shrub species with growing conditions was the main driver in the degradation of such plantings, in particular in the arid conditions in the Steppe of Ukraine. The comprehensive research on the species composition of shelterbelts is essential as it allows us to trace the growth and development of the shelterbelts over time and identify the main trends. The aim of the study is to assess the current state of 90-127-year-old shelterbelts and evaluate the performance of their functions. Materials and Methods The objects of the research were shelterbelts in the Ukrainian ravine steppe. A number of sample plots and study approaches were laid out in the shelterbelts according to standard methods in forestry and agroforestry reclamation; 17 shelterbelts were surveyed and sample plots were established in them. Forest management materials from 1945, 1960, 1985, and 2005 were used. The health condition of trees in the shelterbelts was assessed according to the classification given in the Sanitary Forests Regulations in Ukraine. The shelterbelt damage degree was determined by the health condition index (Ic). The Jacquard species similarity coefficient (Kj) and the Sorensen similarity index (Qs) were used to comparing the species composition and its changes in the studied shelterbelts. Results Shelterbelts were mainly pure stands, with Quercus robur L. and Fraxinus excelsior L. as the main species. Oak stands had satisfactory health condition; however, due to the lack of forestry treatments, there was a decrease in the openness of the shelterbelt vertical profile: the shelterbelts became denser. As of 2021, the species composition of all shelterbelts included 44 species of woody and shrubby plants species, among which the most common were Quercus robur L. (part of all stands), Acer platanoides L., Euonymus europaea L., Acer tataricum L., Acer campestre L., Ulmus minor Mill., Crataegus oxyacantha L., Prunus spinosa L., Fraxinus excelsior L., Fraxinus pennsylvanica Marsh., Swida sanguinea (L.) Opiz. It has been found that the most common "migrating" species are shrubs that inhabit the edge areas of the shelterbelts and make the lower profile of the shelterbelt denser. Dynamic changes in the species composition of field shelterbelts indicate the self-regulation processes: the studied shelterbelts, despite their small width compared to large stands, show signs of a developed forest environment. Conclusions Pure oak shelterbelts in ravine steppe conditions retain biological resilience even at the age of over 120 years. In view of this, the studied shelterbelts created by G. M. Vysotsky, which now reached 93 years old, are potentially able to perform their functions for at least another 30 years, and even more, with proper care. In the severe climatic conditions of the ravine steppe, eight species disappeared from the stand composition: Elaeagnus angustifolia L., Gleditsia triacanthos L., Cotinus coggygria Scop., Cerasus mahaleb (L.) Mill., Tamarix tetrandra Pall. ex Bieb., Salix L., Ptelea trifoliata L., Ribes aureum Pursh and Populus alba L. disappear from the stand composition. Such processes are facilitated by some causes: the short life of species, lack of seed or vegetative regeneration, changes in environmental conditions over time, and inconsistency of bioecological requirements of the species to habitat conditions. The most resilient species for protective afforestation in the ravine steppe conditions are Quercus robur, Ulmus minor, and Acer platanoides as the main species, Acer campestre and Acer tataricum as associated species and Euonymus europaeа, Swida sanguinea, and Prunus spinosa as shrubs. These species are recommended for wide use when creating field shelterbelts in the ravine steppe.